Does soft tissue balancing using intraoperative pressure sensors improve clinical outcomes in total knee arthroplasty? A protocol of a multicentre randomised controlled trial. Issue 5 (10th May 2019) - MacDessi, Samuel J; Bhimani, Aziz; Burns, Alexander W R; Chen, Darren B; Leong, Anthony K L; Molnar, Robert B; Mulford, Jonathan S; Walker, Richard M; Harris, Ian A; Diwan, Ashish; Wood, Jil A
Abstract : Introduction: Soft tissue imbalance is considered to be a major surgical cause of dissatisfaction following total knee arthroplasty (TKA). Surgeon-determined manual assessment of ligament tension has been shown to be a poor determinant of the true knee balance state. The recent introduction of intraoperative sensors, however, allows surgeons to precisely quantify knee compartment pressures and tibiofemoral kinematics, thereby optimising coronal and sagittal plane soft tissue balance. The primary hypothesis of this study is that achieving knee balance with use of sensors in TKA will improve patient-reported outcomes when compared with manual balancing. Methods and analysis: A multicentred, randomised controlled trial will compare patient-reported outcomes in 222 patients undergoing TKA using sensor-guided balancing versus manual balancing. The sensor will be used in both arms for purposes of data collection; however, surgeons will be blinded to the pressure data in patients randomised to manual balancing. The primary outcome will be the change from baseline to 1 year postoperatively in the mean of the four subscales of the Knee Injury and Osteoarthritis Outcome Score (KOOS4 ) that are most specific to TKA recovery: pain, symptoms, function and knee-related quality of life. Secondary outcomes will include the surgeon's capacity to determine knee balance, radiographic and functional measures and additional patient-reported outcomes. Normality of data will be assessed, and a Student's t-test and equivalent non-parametric tests will be used to compare differences in means among the two groups. Ethics and dissemination: Ethics approval was obtained from South Eastern Sydney Local Health District, Approval (HREC/18/POWH/320). Results of the trial will be presented at orthopaedic surgical meetings and submitted for publication in a peer-reviewed journal. Trial registration number: ACTRN#12618000817246